Pengaruh Beauty Vlogger Marketing, Brand Awareness Dan Word Of Mouth Terhadap Keputusan Pembelian Produk Pink Flash (Studi Kasus Pada Masyarakat Delitua Timur - Amelia Putri; Arif Hadian (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This study aims to analyze the influence of Beauty Vlogger Marketing, Brand Awareness, and Word of Mouth on the purchase decision of Pink Flash products among the people of East Delitua. Motivated by the low purchase decision, this associative quantitative study uses a descriptive approach with an unknown population. The sample size was determined to be 100 respondents through purposive sampling and the Cochran formula calculation. Primary data was collected using a Likert scale questionnaire and analyzed using multiple linear regression. The results of the study indicate that, partially, each independent variable (Beauty Vlogger Marketing, Brand Awareness, and Word of Mouth) has a positive and significant effect on purchasing decisions. Simultaneously, all three variables also have a positive and significant influence. The magnitude of this influence is 43.8%, while the remainder is influenced by factors outside the model. Thus, it can be concluded that marketing strategies through beauty vloggers, increased brand awareness, and word of mouth are very important in driving consumer purchasing decisions.